Investigating the Problems of English Speaking of the Students of Islamic Boarding School Program at STAIN Samarinda - Hadijah, Sitti (Dinamika Ilmu, 2014)
This study investigated the students’ ability, the problems and their reasons why they faced problems on English speaking. The triangulation of mixed methods was used in this study. The quantitative data gathered from the speaking test result by involving 130 students of Islamic Boarding School Program and the qualitative data gathered from the questionnaire and interview results from the selected students who meet the criteria. The findings showed that the students’ ability was categorized low (62.93); the students have problems on grammar (42.20%), pronunciation (36.60%), vocabulary (35.20%), fluency (36%) and comprehension (34.40%); the students’ reason in facing the problems on English speaking English were not only having limited knowledge on the components of speaking skills including pronunciation, grammar, vocabulary, fluency and comprehension but also they have own personal reasons, such as shy to perform speaking, lack of self confidence, lack of speaking practice, limited time given for preparation on English speaking test, the difficulties at using and understanding the speaking material found in the English textbook, the environment (dormitory) did not support them to acquire and use English as a medium daily interaction and they preferred to study the Islamic knowledge and Arabic than English. This study indicated that the students’ ability should be increased by giving motivation and taught them with the suitable and interested English speaking materials.